Koinfeksi Virus GB Tipe C (GBV-C) Pasien Human Immunodeficiency Virus (HIV) Rumah Sakit Umum Daerah Dr. Moewardi di Surakarta - Ratna Sariyatun; Afiono Agung Prasetyo; Yulia Sari (Nexus Biomedika, 2014)
Background: Epidemiological data of GB Virus-C (GBV-C) in Indonesia are limited. Information about GBV-C coinfection among HIV patients in Dr. Moewardi General Hospital in Surakarta has also been unknown. Thus, this study is aimed to know the status of GBV-C coinfection among HIV patients in Dr. Moewardi General Hospital in Surakarta. Methods: Blood samples from 44 HIV patients in Dr. Moewardi General Hospital were subjected to viral RNA isolation. Complementary DNA (cDNA) was synthesized from the isolated RNA and used as template for nested polymerase chain reaction (PCR) detecting the 5'-non-translated region of GBV-C. The amplicons were electrophoresed in 2% agarose gel and then visualized under UV and interpreted. Results: GBV-C RNA was detected in seven samples from HIV patients (15.9%, 7/44). All patients with GBV-C coinfection were women. Conclusions: The frequency of GBV-C RNA coinfection among HIV patients in Dr. Moewardi General Hospital in Surakarta is 15.9% (7/44). Keywords: GBV-C, HIV, Surakarta